Analysis Of Coliform And E-Coli Pollution In Groundwater In The Environment Of Cattle Farming Communities In Jetis District, Bantul Regency, Yogyakarta - Yolinda Matulessy*; M. Widyastuti; Suwarno Hadisusanto (Riwayat: Educational Journal of History and Humanities, 2023)
Water is one of the most important natural resources for all living organisms including humans for drinking, food production, domestic purposes, and other development. Water also has a negative side, in that it can transmit infectious diseases, which are caused by the infiltration of pathogenic bacteria. This study aimed to analyze groundwater pollution based on Total Coliform and E. Coli, analyze the impact of Total Coliform and E. Coli on the health of cattle breeders, and formulate strategies to reduce groundwater pollution caused by Coliform and E. Coli. This research uses field studies which include field observations, sampling, laboratory analysis, interviews, and documentation. The research location is in Jetis District, Bantul Regency, Yogyakarta and there are six sample points with 24 groundwater samples. Sampling of water for bacteriological tests uses the instantaneous water sampling method (grab sampling). Based on the results of laboratory analysis, it is known that the content of Total Coliform and E.coli at a distance of 10 meters has exceeded the quality standard, but at point 5 with the sample code T5K it still meets the Total Coliform quality standard. At a distance of 10 meters, it is known that four points pass the Total Coliform quality standard threshold and all points pass the E. coli quality standard threshold. The impact of groundwater pollution due to Coliform and E.coli bacteria on public health is known to be 78.5% or from 14 respondents 11 respondents experienced diarrhea. The recommended strategy is a defensive strategy or defense by minimizing weaknesses and preventing threats.